Cross-Regional Energy Strategies: Evaluating Japan’s Power Blueprint for Nigeria’s Needs - Mutiat S. YISA (FUDMA Journal of Engineering and Technology, 2025)
The urgent need for sustainable, secure, and diversified energy sources remains a pressing concern for both developed and developing economies. Japan, an advanced economy with limited domestic energy resources, has adopted a power generation strategy centered around nuclear energy, liquefied natural gas (LNG), and wind. Conversely, Nigeria, a resource-rich yet energy-deficient country, continues to struggle with energy access and sustainability. This paper conducts a comparative assessment of Japan's proposed power generation strategy and evaluates its viability and applicability in the Nigerian context. Using criteria such as economic feasibility, environmental sustainability, energy security, and socio-political acceptability, the study finds that adapting elements of Japan’s strategy, particularly its emphasis on LNG, nuclear, and wind, could significantly enhance Nigeria’s energy mix. However, key contextual differences such as geography, regulatory maturity, infrastructure, and public perception must be carefully considered for successful policy transfer.
Keywords: Energy strategy, renewable energy, nuclear power, Nigeria, Japan energy mix.